2012
DOI: 10.1007/s10151-012-0871-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional luminal imaging probe: a new technique for dynamic evaluation of mechanical properties of the anal canal

Abstract: BackgroundThe muscle structures surrounding the anal canal are of major importance in maintaining continence but their anatomy and function vary along its length. Standard manometry does not provide detailed information about mechanical properties of the anal canal. A new functional luminal imaging probe (FLIP) has been developed for this purpose. The aim of our study was to investigate whether FLIP allows detailed evaluation of dynamic biomechanical properties along the length of the anal canal.MethodsThe in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 30 publications
1
51
0
1
Order By: Relevance
“…This is clearly an advantage, since the structure and surrounding tissues are heterogeneously distributed along the longitudinal axis. Variations in distensibility along the sphincter can be explained by the heterogeneous anatomy and active muscle function of the sphincters [39,54,56,57,69]. In addition to assessment of sphincter wall heterogeneity caused by changes in the mechanical properties and muscle tone, FLIP measurement is also capable of showing alterations caused by diseases, such as achalasia [47,68], systemic sclerosis [57], and idiopathic fecal incontinence [56].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is clearly an advantage, since the structure and surrounding tissues are heterogeneously distributed along the longitudinal axis. Variations in distensibility along the sphincter can be explained by the heterogeneous anatomy and active muscle function of the sphincters [39,54,56,57,69]. In addition to assessment of sphincter wall heterogeneity caused by changes in the mechanical properties and muscle tone, FLIP measurement is also capable of showing alterations caused by diseases, such as achalasia [47,68], systemic sclerosis [57], and idiopathic fecal incontinence [56].…”
Section: Discussionmentioning
confidence: 99%
“…So far, only four studies have been published [54][55][56][57]. In vitro tests have shown FLIP distensibility measurements to have great validity and reproducibility [54].…”
Section: Anal Sphinctersmentioning
confidence: 99%
See 2 more Smart Citations
“…Luft et al, 14 studied the use of EndoFLIP in assessing anal canal properties in healthy individuals. The authors concluded that the upper part of the anal canal is the most compliant and that the least distensible part is the mid-anal canal region, which contributes the most to resting anal continence.…”
Section: Anal Sphincter Evaluation and Fecal Incontinencementioning
confidence: 99%